Quantitative prediction of molecular adsorption: structure and binding of benzene on coinage metals - Liu, Wei; Maaß, Friedrich; Willenbockel, Martin; Bronner, Christopher; Schulze, Michael; Soubatch, Serguei; Tautz, F. Stefan; Tegeder, Petra; Tkatchenko, Alexandre (Physical review letters, 2015)
Interfaces between organic molecules and solid surfaces play a prominent role in heterogeneous catalysis, molecular sensors and switches, light-emitting diodes, and photovoltaics. The properties and the ensuing function of such hybrid interfaces often depend exponentially on molecular adsorption heights and binding strengths, calling for well-established benchmarks of these two quantities. Here we present systematic measurements that enable us to quantify the interaction of benzene with the Ag(111) coinage metal substrate with unprecedented accuracy (0.02 Å in the vertical adsorption height and 0.05 eV in the binding strength) by means of normal-incidence x-ray standing waves and temperature-programed desorption techniques. Based on these accurate experimental benchmarks for a prototypical molecule-solid interface, we demonstrate that recently developed first-principles calculations that explicitly account for the nonlocality of electronic exchange and correlation effects are able to determine the structure and stability of benzene on the Ag(111) surface within experimental error bars. Remarkably, such precise experiments and calculations demonstrate that despite different electronic properties of copper, silver, and gold, the binding strength of benzene is equal on the (111) surface of these three coinage metals. Our results suggest the existence of universal binding energy trends for aromatic molecules on surfaces.